Studi Pengaruh Permainan Tradisional Rangku Alu terhadap Kebugaran Jasmani Siswa dengan Pendekatan Statistik Nonparametrik - Nay, Florianus Aloysius; Fallo, Sefri Imanuel; Talan, Rudobertus; Rajagukguk, Christin P. M. (SPRINTER: Jurnal Ilmu Olahraga, 2024)
The objectives of the study were (1) to determine whether there were differences before and after training in the traditional Rangku Alu game on the physical fitness of students; (2) to increase the height of students' jumps in the high jump sport through the traditional Rangku Alu game. The method used in the study was the experimental research method. In this case, what will be studied is the effect of the traditional Rangku Alu game on physical fitness in students of the Osmok Kupang Inpres Elementary School with a one-group design that was given pretest and posttest treatment. Based on the results of the analysis and discussion, it was found that there was a significant difference between the pre-test and post-test results as indicated by the Z value = -2.940 dan p = 0.003. These results indicate that training using the traditional Rangku Alu game can significantly improve jump height performance. Overall, this study shows that the traditional approach can be an innovative method in supporting the improvement of students' physical fitness.